VPAC targeted optical imaging assay (VPAC assay) of voided urine for management of patients with persistently elevated PSA - Thakur, Mathew L.; Trabulsi, Edouard John; Dale, Emma; Singh, Vivek; Chhabra, Anupriya; Dahlgren, Olivia; Kolesnikov, Oleksandr; Wang, Kerith; Gomella, Leonard G. (JCO global oncology, 2023)
124 Background: Nearly 50% of patients with persistently elevated PSA (PEP) have prostate cancer (PCa) despite previous negative biopsy. However not all patients agree to undergo repeat, invasive trans rectal or trans perineal prostate biopsy (PB). To identify men at high risk of PCa, the need is unmet of other reliable diagnostic methods. The goal of this investigation was to determine if the VPAC assay, which is being developed in our laboratory and detects PCa efficiently, by imaging PCa cells shed in voided urine, collected without digital rectal examination (DRE), can address the common clinical dilemma of when or if to repeat biopsy on PEP subjects. Methods: PEP patients (N=21, 55-75 yr. PSA 2.8 – 42 ng/ml), scheduled for PB and signed informed consent form were enrolled. They provided pre and clinically required, post DRE urine. VPAC assay was performed on both urine samples from each patient. VPAC, a genomic receptor, encodes G protein and expresses in high density on all malignant PCa cells, was targeted with TP4303, a biomolecule with fluorophore, designed in our laboratory with high affinity (Kd, 3.1x10 -9 M) for VPAC. Urine was centrifuged, cells on a glass slide fixed, incubated with TP4303 and excess was washed. Cells were then examined under a microscope. TP4303 fluorescence around cell nucleus allowed to identify malignant PCa cells. For urine collected post DRE, MDx Health assay, approved by FDA and determines mRNA levels of DXL1 and HOXC6 biomarkers and indicates risk of PCa, was also performed. Results were compared with gold standard histopathology of tissues acquired through PB, and evaluated statistically. Results: Of 21 PEP patients, who underwent PB, three (14%) had histopathologically proven, clinically significant PCa with Grade Group 2. All three (100%) patients were correctly identified as positive for PCa by the VPAC assay, while MDx reported low risk for two (9.5%) and high risk for one (53%). Of the remaining 18, histologically negative subjects, VPAC assay was disconcordant in five (28%), with positive for PCa. In these five patients, MDx also reported moderate to high risk (40%-59%). Of the remaining 13 histologically negative PCa patient, all (100%) had concordant results with VPAC assay while MDx reported low risk in 2 patients and moderate to high risk (range 30% to 90%) in other eleven. Results with sensitivity and specificity of the assays are given in the table. Conclusions: The VPAC assay data, in this small exploratory cohort, appear promising as an additional diagnostic in the clinical management of PEP patients, minimizing the number of unnecessary invasive PBs and eliminating possible overtreatment. Work is in progress. Support: NIH 5R01CA249921. [Table: see text]